Enzymatic Synthesis of Ascorbyl Palmitate in Organic Solvents: Process Optimization and Kinetic Evaluation - Lerin L. A.; Richetti A.; Dallago R.; Treichel H.; Mazutti M. A.; Oliveira J. V.; Antunes O. A. C.; Oestreicher E. G.; de Oliveira D. (Food and Bioprocess Technology, 2012)
This work is focused on the optimization of reaction parameters for the synthesis of ascorbyl palmitate catalyzed by Candida antarctica lipase in different organic solvents. The sequential strategy of experimental designs proved to be useful in maximizing the conditions for product conversion in tert-butanol system using Novozym 435 as catalyst. The optimum production were achieved at ascorbic acid to palmitic acid mole ratio of 1:9, stirring rate of 150 rpm, 70 °C, enzyme concentration of 5 wt.% at 17 h of reaction, resulting in an ascorbyl palmitate conversion of about 67%. Reaction kinetics for ascorbyl palmitate production showed that very satisfactory reaction conversions (~56%) could be achieved in short reaction times (6 h). The kinetic empirical model proposed showed ability to satisfactory represents and predict the experimental data. © 2010 Springer Science + Business Media, LLC.